A Survey of Four Indo-Pakistani Scholars’ Perspectives on the Islam-Democracy Discourse (American Journal of Islam and Society, 2012)
In contemporary times, the relationship between Islam and democracy –democracy and its Islamic heritage and the process of democratization inMuslim societies, and other related themes – is a hotly debated and discussedtopic. Throughout the Muslim world – from South, Southeast and CentralAsia to Middle East and North Africa – Muslim thinkers have undertakenthe effort of working within and cooperating with existing political regimesand authorities ‒ from republics, monarchies and authoritarian dictatorshipsto pluralistic and relativity homogeneous societies. With the desirefor democratization, along with the continuing resurgence of Islam in a dynamicglobal context, the demand and desire for democracy is widespread.Two of the major developments in the final decades of the twentiethcentury to present are “religious resurgence” and “democratization.” Thedebate over democracy and democratization in the Muslim societies, itsdefinition and fundamentals, has continued for a long time, but, as it hasacquired an impetus in recent years, and this debate has become highlyintensified.The Muslim world at present is the most diverse in the forms of the politicalsystems it employs. It has traditional and constitutional monarchies,dictatorships, Islamic republics, and secular and some liberal democracies‒ and due to the diverse interpretations of its laws and sources of law, Islampossesses intellectual and ideological resources that can provide justificationfor a wide range of governing models from monarchy to democracy ...